Shelter in Place: Pandemic Prudentialism and Park Space in Toronto/Tkaronto - De Lisio, Amanda; Fusco, Caroline; Woodworth, Steph; Taha-Thomure, Raiya (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
In this article, we interrogate the representation and construction of public park space in a settler colonial city: Toronto/Tkaronto. First, we draw on the relationship between urban neoliberalism and prudentialism to demonstrate the way public health authorities in Toronto/Tkaronto promoted a neoliberal ideology of prudentialism that emphasized individual action (e.g., social distancing, personal hygiene, sheltering in place) in response to the COVID-19 pandemic. Second, we consider the extent to which this response congealed and combined with broader anxieties that were used to manage more than the virus. We focus specifically on the way these anxieties took hold in public park space, and in particular the response to encampment communities. We theorize prudentialism, as an instrument of the white settler state, to interrogate the twin processes of organized abandonment and organized violence (Gilmore 2022), which were made visible in the treatment of unhoused people amidst the pandemic in an affluent and seemingly progressive city in a nation now known as Canada. Recognizing that COVID-19 has afflicted global cities marred by real estate speculation and the continual reliance on the commodification of Indigenous Land, which has made homelessness and urban displacement a lived condition for some, we argue that public health crises result not from—and thereby cannot be solved by—prudential responsibilization, but from the willful ignorance of the neoliberal, capitalist white settler [real estate] state (Stein 2019).